The Association of Plant-Based Diet With Cardiovascular Disease and Mortality: A Meta-Analysis and Systematic Review of Prospect Cohort Studies - Quek, Jingxuan; Lim, Grace; Lim, Wen Hui; Ng, Cheng Han; So, Wei Zheng; Toh, Jonathan; Pan, Xin Hui; Chin, Yip Han; Muthiah, Mark D.; Chan, Siew Pang; Foo, Roger S. Y.; Yip, James; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between plant-based diets and cardiovascular disease (CVD) remains poorly characterized. Given that diet represents an important and a modifiable risk factor, this study aimed to assess (1) the relationships between the impact of adherence to plant-based diets on cardiovascular mortality, incident CVD, and stroke; (2) if associations differed by adherence to healthful and less healthful plant-based diets. Methods and Findings: MEDLINE and EMBASE databases were searched up to May 2021. Studies assessing CVD outcomes with relation to plant-based dietary patterns or according to plant-based dietary indices (PDI) were included. A meta-analysis of hazard ratios (HR) was conducted using DerSimonian and Laird random effects model. Thirteen studies involving 410,085 participants were included. Greater adherence to an overall plant-based dietary pattern was significantly associated with a lower risk of cardiovascular mortality (pooled HR: 0.92, 95% CI: 0.86–0.99 p = 0.0193, I2 = 88.5%, N = 124,501) and a lower risk of CVD incidence (pooled HR: 0.90, 95% CI: 0.82–0.98, p = 0.0173, I2 = 87.2%, N = 323,854). Among the studies that used PDI, unhealthful plant-based diets were associated with increased risk of cardiovascular mortality (pooled HR: 1.05, 95% CI: 1.01–1.09, p = 0.0123, I2 = 0.00%, N = 18,966), but not CVD incidence. Conversely, healthful plant-based diets were associated with decreased CVD incidence (pooled HR: 0.87, 95% CI: 0.80–0.95, p = 0.0011, I2 = 57.5%, N = 71,301), but not mortality. Vegetarians also had significantly lower CVD incidence (HR: 0.81, 95% CI: 0.72–0.91, p = 0.0004, I2 = 22.2%, N = 16,254), but similar CVD mortality or stroke risk when compared to the meat-eaters. Conclusion: To date, this comprehensive study examines the effects of a plant-based diet on major clinical endpoints using more holistic PDIs. These findings highlight the favorable role of healthful plant-based foods in reducing cardiovascular mortality and CVD.